Can upward-facing digital camera images be used for remote monitoring of forest phenology?. (29th January 2018) - Wilkinson, Matthew; Eaton, Edward L; Morison, James I L
Abstract: Digital hemispherical photography is a valuable method for monitoring changes in the biosphere's response to climate change. In forests, cameras have often been fitted to existing towers and masts. However, such towers are logistically difficult and expensive to install. Ground-based automatic camera systems offer an alternative that removes the barriers associated with above-canopy photography, but to date there have been few comparisons between upward- and downward-facing images at the same site. This study addresses this issue, by comparing a pair of cameras, one ground-based, one tower-based, viewing the same trees in a deciduous oak ( Quercus robur L.) plantation forest in south-eastern England. Over 6 years, the upward-facing ground-based camera system was able to detect key spring phenological events to the same extent as the more usual downward-facing camera (mean difference of 2 days for green-up date). However, the upward- and downward-facing systems were less well-matched in detecting specific events at the end of the growing season, although both systems displayed similar temporal trends. Upward-facing cameras can therefore act as a reliable and comparable alternative to tower-based phenocam systems, as well as being more suitable for wider spatial coverage without the need for expensive installation infrastructure. In addition to the increased ease of access with upward-facing camera systems, the images from them also allow canopy structural dynamics such as canopy closure to be estimated.